Enhancing customer loyalty to mobile instant messaging: Perspectives of network effect and self-determination theories. Issue 5 (August 2018) - Tseng, Fan-Chen; Pham, Thi Tuan Linh; Cheng, T.C.E.; Teng, Ching-I
Highlights: This study examines how network effect impacts loyalty to mobile instant messaging. Perceived complementarity was positively related to customer-perceived values. Customer-perceived values were positively related to need satisfaction and loyalty. Abstract: Mobile instant messaging (MIM) apps are popular information and communication technologies (ICTs). As known for ICTs, network effect variables such as perceived network size and perceived complementarity are important for determining user loyalty. However, there is insufficient research on why they are determinants, i.e., knowing the underlying mechanism. Grounded in network effect and self-determination theories, we study such underlying mechanism. Based on an analysis of responses from an online survey of 292 participants using structural equation modelling, we find that the network effect variables of perceived network size and perceived complementarity are positively related to three user-perceived values, namely user-perceived functional, self-expressive, and social values. They are, in turn, positively related to satisfaction of the needs for competence, autonomy, and relatedness, respectively, that further leads to user loyalty. This study contributes to the MIM literature by being the first to use the three user-perceived values and satisfaction of the three needs as novel process variables to construct a model for explaining the impacts of network effect variables on user loyalty to MIM apps. This study provides the insight that MIM providers can more effectively enhance user loyalty by providing the three values that users appreciate and satisfying the three needs, when increasing and advertising their network sizes and availability of complementary offerings.